A multidisciplinary approach for the characterization of the coastal marine ecosystems of Monte Di Procida (Campania, Italy). Issue 1 (15th November 2016) - Mangoni, Olga; Aiello, Giuseppe; Balbi, Simona; Barra, Diana; Bolinesi, Francesco; Donadio, Carlo; Ferrara, Luciano; Guida, Marco; Parisi, Roberta; Pennetta, Micla; Trifuoggi, Marco; Arienzo, Michele
Abstract: A multidisciplinary survey was carried out on the quality of water and sediments of a coastal protected marine area, embedded between the inputs from Bagnoli steel plant to the south and a sewage plant, Volturno River and Regi Lagni channel to the north. The study integrated chemical-sedimentological data with biological and ecotoxicological analyses to assess anthropogenic pressures and natural variability. Data reveal marked differences in anthropogenic pollution between southeastern and northwestern zone, with the north affected by both inorganic and organic flows and the south influenced by levels of As, Pb and Zn in the sediments above law limits, deriving from inputs of the Bagnoli brownfield site. Meiobenthic data revealed at south higher relative abundance of sensitive species to pollution and environmental stress to the south, i.e. Lobatula lobatula and Rosalina bradyi, whereas to the north relative abundance of stress tolerant Quinqueloculina lata, Quinqueloculina pygmaea and Cribroelphidium cuvilleri were determined. Highlights: Multi-disciplinary approach for the study of a coastal marine environment Relationships between physico-chemical and biological features of waters and sediments Multivariate statistical analysis and differences in anthropogenic pollution